Circular RNA circ-PVT1 contributes to paclitaxel resistance of gastric cancer cells through the regulation of ZEB1 expression by sponging miR-124-3p. Issue 12 (24th December 2019) - Liu, Yan-yan; Zhang, Li-ying; Du, Wen-zhen
Abstract: Gastric cancer (GC) is the fifth most commonly diagnosed malignancy. Paclitaxel (PTX) is an effective first-line chemotherapy drug in GC treatment, but the resistance of PTX attenuates the therapeutic effect. Circular RNA circ-PVT1 can exert the oncogenic effect in GC. But the function of circ-PVT1 involved in PTX resistance of GC is still unknown. In the present study, the expression levels of circ-PVT1, miR-124-3p and ZEB1 in PTX-resistant GC tissues and cells were detected by quantitative real-time polymerase chain reaction (RT-qPCR). PTX resistance in PTX-resistant cells was assessed by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT) assay. The protein levels of Zinc finger E-box binding homeobox 1 (ZEB1), P-glycoprotein (P-gp) and glutathione S-transferase (GST-π) were detected by Western blot assay. Cell apoptosis and invasion were measured in PTX-resistant cells by flow cytometry and transwell invasion assays, severally. The interaction between miR-124-3p and circ-PVT1 or ZEB1 was predicted by starBase software, and then verified by the dual-luciferase reporter assay. The role of circ-PVT1 in PTX resistance of GC in vivo was measured by xenograft tumor model. Our results showed that circ-PVT1 expression was up-regulated in PTX-resistant GC tissues and cells. Circ-PVT1 down-regulation enhanced PTX sensitivity in PTX-resistant GC cells by negatively regulating miR-124-3p. ZEB1 served as a direct target of miR-124-3p. Circ-PVT1 enhanced ZEB1 expression by sponging miR-124-3p. Circ-PVT1 knockdown increased PTX sensitivity of GC in vivo. Taken together, our studies disclosed that circ-PVT1 facilitated PTX resistance by up-regulating ZEB1 mediated via miR-124-3p, suggesting an underlying therapeutic strategy for GC.